A Novel Strategy to Sustain and Improve Crop Productivity under Saline-prone Arable Lands - Maiti, Ratikanta; Vidyasagar, P. (International Journal of Bio-resource and Stress Management, 2023)
Over 800 mha land throughout the world are affected with salinity and the rest with sodicity (434 mha). Salinity is one of the major concerns with water used in irrigation. About 20% of irrigated agriculture in the world is adversely affected by salinity (Flowers and Yeo, 1995). Most of the grain crops and vegetables are highly susceptible to soil salinity even at a level of soil EC<4 ds m-1. Salinity threshold values vary among species (Maas cited by Chinnusamy et al., 2005). Research have been concentrated on management strategy, progress on salinity tolerance of some crops, its effect, variation and selection and mechanism of tolerance (a review by Gonzalez-Rodriguez and….